Korelasi Antara Motivasi Dan Disiplin Dalam Pembelajaran Terhadap Prestasi Belajar Siswa Kelas VII Di MTs Ma’arif Udanawu Blitar - Septi Yuliasari; Yudi Krisno Wicaksono (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research is motivated by the current decline in student learning achievement because they still carry online habits caused by Covid-19. This happens because they lack motivation and reduced discipline due to being online for too long. Therefore, it is necessary to provide motivation at the beginning of learning and it is necessary to tighten student discipline so that they can return to their original condition or be better. The purpose of this research is to determine the relationship between motivation in learning and the learning achievement of class VII students at MTs Ma'arif Udanawu, Blitar Regency. To find out whether there is a correlation between discipline and learning and the learning achievement of class VII students at MTs Ma'arif Udanawu, Blitar Regency. To determine the relationship between motivation and discipline on the learning achievement of class VII students at MTs Ma'arif Udanawu, Blitar Regency.This research uses quantitative descriptive methods. In this research, the subjects were class VII students at MTs Ma'arif Bakung Udanawu, Blitar Regency, totaling 373 students with a sample of 93 students. The approach used in data collection was distributing questionnaires to class VII students. Data analysis methods include research instrument tests, classical assumption tests, and multiple linear regression tests. The research results identified that 1) There is a partial positive and significant influence between motivation and learning achievement as shown by the t-count which is greater than the t-table (1.715 > 1.661). 2) Partially there is also a positive and significant influence between discipline and learning achievement as seen from the t-count results which exceed the t-table (1.843 > 1.661). 3) Simultaneously there is a positive and significant influence between motivation and discipline on learning achievement as indicated by Fcount greater than Ftable (4.835 > 3.10). 4) The contribution of the independent variable to the dependent variable is 31.8%. The conclusion of this research is that there is a positive and significant relationship between learning motivation and learning discipline and learning achievement.